FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN (PBB) PADA SEKTOR SAWAH DI PEDESAAN - Aan Apriyan Anugrah (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
Taxpayer compliance in paying Land and Building Tax (PBB) in the rice field sector has a very important role in maintaining regional income and supporting development in the agricultural sector. With this aim to analyze various factors that influence various levels of taxpayer compliance in PBB payments in the rice fields. Supervision by the local government and disclosure of information regarding the importance of paying taxes by taxpayers, especially in rural areas, will provide awareness or compliance by taxpayers in making tax payments, so that taxpayers have sufficient understanding about taxes.